INFLUENCE OF BOTH ELECTRIC AND MAGNETIC FIELDS ON THE BOUND POLARON IN AN ANISOTROPIC QUANTUM DOT - CHEN, SHI-HUA; XIAO, JING-LIN (International journal of modern physics. B, Condensed matter physics, statistical physics, applied physics, 2008)
The binding energy of a bound polaron in an anisotropic quantum dot (QD) subject to electric and magnetic fields along the growth axis has been investigated by using a variational method of Pekar type, taking into account the electron-bulk LO-phonon interaction. The results show that the binding energy decreases with increasing electric field strength and increases with increasing confinement strengths in the lateral and the longitudinal direction, the magnetic field strength, and the Coulomb potential.